Nurses’ work engagement and perceived public health impact in post-pandemic China: a cross-sectional pathway study of knowledge translation, practice improvement, and community-academic partnerships - Shan Wang; Chunmei Li; Qinfang Liu (Frontiers in Public Health, 2026)
Background Public health nursing remains important to post-pandemic health-system resilience because nurses connect clinical care with prevention and community support. However, it remains unclear how nurses’ work engagement is associated with perceived public health contribution through evidence use and practice improvement. Objective This study examined associations among nurses’ work engagement, community–academic partnerships, knowledge translation, practice improvement, and nurses’ perceived public health impact. Methods: A quantitative cross-sectional survey was conducted among registered nurses in mainland China between 15 January 2026 and 31 March 2026. A total of 450 questionnaires were distributed, and 420 valid responses were included in the analysis. The five constructs were measured using multi-item five-point Likert scales. Data were analyzed using descriptive statistics, reliability and validity assessment, hierarchical regression, partial least squares structural equation modeling, bootstrapped indirect-effect analysis, subgroup analysis, and sensitivity checks. Results The five constructs showed acceptable internal consistency, convergent validity, and discriminant validity. Nurses’ work engagement was positively associated with knowledge translation; knowledge translation was positively associated with practice improvement; and practice improvement was positively associated with perceived public health impact. Community–academic partnerships were positively associated with both knowledge translation and practice improvement. Conclusion Nurses’ work engagement was indirectly associated with perceived public health impact through knowledge translation and practice improvement. These findings support an integrated, association-based pathway linking workforce engagement, evidence use, academic–practice collaboration, and practice improvement, while the cross-sectional design precludes causal inference.